Cyberphilosophy: The Intersection of Philosophy and Computing - Moor, James H.; Bynum, Terrell Ward (Blackwell, 2002)
Keywords: Data processing; Philosophy; dept.phi; faculty_collection

Heidegger and Practical Philosophy - Raffoul, François; Pettigrew, David (State University of New York Press, 2002)
Investigating the extent to which Heidegger's thought can be read as a crucial resource for practical philosophy and the articulation of an ethos for our time, leading scholars offer a sustained and intensive focus on Heidegger's thought of praxis.–(Source of description unspecified.)
Keywords: Heidegger; Martin; 1889-1976; Ethics; Political science; Philosophy; Practice (Philosophy); dept.phi; faculty_collection

Introduction to cyberphilosophy - Moor, James H.; Bynum, Terrell Ward (Metaphilosophy, 2002)
9 citations (Crossref) [2023-10-31] Citation Key Alias: pop00167 tex.type: [object Object]
Keywords: dept.phi